Threat to flooding risk in flatlands hydrological systems under climate change scenarios: application to the "Las Encadenadas" system (Cuadernos del CURIHAM is a half-year publication of the Centro Universitario de Rosario of hydro-environmental research directed by Adelma Mancinelli. It is dedicated to spreading the results of basic and applied research as well as technological innovations on the realm of hidro-environmental issues. It may include field study results, interdisciplinary studies or studies on the state of art on the field: basic hydraulics, fluvial and hydrodinamics, superficial and underground hydrology, urban and stochastic hydrology, planning and management of hydric resources, environmental evaluation, pollution and quality of the water, politics and water legislation, regional hydro-environmental management, hydraulic construction, methods and techniques and everything related to hydro-environmental sciences., 2024)
In the present work the threat associated with different climate change (CC) scenarios on the flooding risk of the non-typical hydrological system called “Las Encadenadas” is studied. The basin is located in the southern part of Santa Fe province in Argentina. The tools and methodologies used are based on geomatics. Regarding representations of the system behavior, a physically based distributed hydrologic-hydraulic model is used. The main results are the quantification and mapping of water surfaces and flows, the permanence of surface water and its proximity to urban areas and road networks, for recurrences with and without consideration of the CC effect. For the most discouraging conditions: 100-year recurrence, quasi-saturated soil and CC coefficient of 1.30, we obtained 19.92% of the system surface area occupied with water, peak flows of about 320 m³/s in the closing section, water runoff of 11.6% in the first 24 hours and a total of 202 sections of road networks with water in the vicinity. A new delimitation of the system was obtained and improvements were made in the zoning and regulation of land use in flood-prone areas in different towns, in accordance with Law No. 11730.
Keywords: Flatlands Hydrological Systems; Distributed and Physically Based Hydrological-Hydraulic Model; Geomatics Tools; Las Encadenadas; Climate Change